Continuous monitoring of noise levels in the Gulf of Catania (Ionian Sea). Study of correlation with ship traffic. Issue 1 (15th August 2017) - Viola, S.; Grammauta, R.; Sciacca, V.; Bellia, G.; Beranzoli, L.; Buscaino, G.; Caruso, F.; Chierici, F.; Cuttone, G.; D'Amico, A.; De Luca, V.; Embriaco, D.; et al.
Abstract: Acoustic noise levels were measured in the Gulf of Catania (Ionian Sea) from July 2012 to May 2013 by a low frequency (< 1000 Hz) hydrophone, installed on board the NEMO-SN1 multidisciplinary observatory. NEMO-SN1 is a cabled node of EMSO-ERIC, which was deployed at a water depth of 2100 m, 25 km off Catania. The study area is characterized by the proximity of mid-size harbors and shipping lanes. Measured noise levels were correlated with the passage of ships tracked with a dedicated AIS antenna. Noise power was measured in the frequency range between 10 Hz and 1000 Hz. Experimental data were compared with the results of a fast numerical model based on AIS data to evaluate the contribution of shipping noise in six consecutive 1/3 octave frequency bands, including the 1/3 octave frequency bands centered at 63 Hz and 125 Hz, indicated by the Marine Strategy Framework Directive (2008/56/EC). Highlights: NEMO-SN1 is a cabled node of EMSO-ERIC, deployed at 2100 m in Western Ionian Sea. Acoustic noise (¡1 kHz) was continuously measured from July 2012 to May 2013. SPL was measured in 1/3 octave frequency bands. An AIS-based simulation of ship noise data was run and compared with acoustic data. Experimental values of SPL in the area are largely attributed to ship traffic.